(untitled) - Ayres, Clarence Edwin (Kalamazoo, Michigan, 1978)
The publication of this new edition of The theory of economic progress is of vital importance to a large number of concerned scholar. many of them have offered their full support of our efforts to again make it available for themselves and thier classes and for successive generations of students.
Keywords: Economics,Kinh tế học